Good Corporate Governance in Credit Restructuring as an Effort to Mitigate Legal Risk - Amanda Fitriani Eka Putri; Ariawan Gunadi (Program magister Kenotariatan Fakultas Hukum Universitas Lambung Mangkurat, 2025)
In the banking sector, credit distribution serves as the core business activity and primary source of revenue, yet it also exposes banks to legal and financial risks that may disrupt institutional stability. Credit restructuring is a strategic recovery measure that must be carried out in accordance with Good Corporate Governance (GCG) principles to prevent further legal complications. This study aims to analyze the implementation of GCG in credit restructuring as a legal risk mitigation mechanism for commercial banks in Indonesia. The research employs a normative juridical method using both statutory and conceptual approaches. The findings demonstrate that applying GCG principles enhances accountability in restructuring decisions through accurate verification and transparent disclosure of debtor information to relevant stakeholders. The principles of independence and prudence serve to prevent conflicts of interest and moral hazard that could lead to civil disputes between banks and debtors. Furthermore, proper documentation and adherence to Financial Services Authority regulations reduce the likelihood of administrative sanctions related to inaccurate reporting or asset quality misassessment. At the same time, fairness in the negotiation process strengthens public trust and minimizes reputational risks that may result in significant financial consequences for banks. Therefore, comprehensive implementation of GCG principles is essential to ensure effective and sustainable credit restructuring governance, ultimately contributing to stronger resilience and long-term stability of the Indonesian banking sector.